Linkage control method of fully mechanized mining equipment based on thousand eyes intelligent analysis system - Xu LI; Wei YANG; Yun SHI; Jie LI; Bo DONG (Meikuang Anquan)
The fully mechanized mining face system is complex and large, and the equipment is highly correlated. The reliability of the intelligent fully-mechanized coal mining equipment system has gradually become the key factor restricting the intelligent safe and efficient mining of the working face. Based on this, a linkage control method of fully mechanized mining equipment based on a thousand eyes intelligent analysis system is proposed and developed. By laying several new generation high-definition cameras in the area of fully mechanized mining surface, the fully mechanized mining surface can be visualized in all directions without dead corners to realize the intelligent identification and protection of the whole process of personnel intrusion in the fully mechanized mining face area, personnel intrusion in the dangerous area of support shifting, personnel intrusion in the shearer cutting area, personnel dressing, anti-collision monitoring of coal machine and support, intelligent monitoring of scraper conveyor operating conditions, etc. From the perspective of comprehensive real-time monitoring of fully mechanized mining surface, equipment operating status, personnel safety behavior, etc., with the help of AI+AR hybrid augmented reality technology and combined with the real-time operating conditions of fully mechanized mining surface equipment, intelligent control and collaborative services are used to realize intelligent identification and real-time warning of safety behaviors of equipment and personnel in the fully mechanized mining surface area. A standardized linkage control method of “real-time screen acquisition, rapid information identification, system early warning record, remote warning and equipment joint control” is formed to monitor the whole process of equipment operation and personnel behavior, effectively predict and prevent potential safety hazards, and maximize the safe and efficient mining of fully mechanized mining face.